Dependence on the distribution of valuable elements and chemical characterizations based on different particle sizes of high alumina fly ash. (1st May 2021) - Gong, Yanbing; Sun, Junmin; Zhang, Yinmin; Zhang, Yongfeng; Zhang, Ting-an
Highlights: Metal oxides decreased as the particle sizes of HAFA increasing, while non-metal oxides showed the opposite trends. Mullite and corundum are more abundant in the smaller sizes, but the amorphous phase and quartz majorly in the larger. Grinding has little effect on the desilication efficiency. The glass phase Al2 O3 affects the separation of aluminum and silica. Abstract: Understanding the influence of the particle size on the distribution of various elements of high alumina coal fly ash (HAFA) is of significance to the utilization of valuable elements in fly ash. The distribution of valuable elements and the chemical characterizations of various particle sizes of HAFA were analyzed using X-ray diffraction (XRD), scanning electron microscopy (SEM), and Brunauer–Emmett–Teller (BET) analysis etc. in this work. It indicated that the contents of most of the metal oxides, including Al2 O3, Fe2 O3, CaO, Ga2 O3, TiO2, and Li2 O, decreased as the particle sizes of HAFA increasing. The contents of the nonmetal oxides, including SiO2 and organics, however, increased with the sizes increasing. For the phases distribution, the spherical mullite crystalline phase and the corundum phase were more abundant in the smaller particle sizes, while the amorphous glass phase and quartz were more abundant in the larger particle sizes. In addition, the desilication efficiency increased from 38.08% to 39.30% though mechanical pretreatment method. Interestingly, it was observed that the glass phase Al2 O3 reacted with the sodium silicate solution to form zeolites, which accounted for a 22.85% of the mass after desilication. Classification may be an important pretreatment step in the recovery of valuable elements from HAFA due to the differences between the different granularities.